Sobre la relación entre teoría y la práctica en los contenidos de teoría general del derecho - Aldao, Martín M. (2014)
This paper pose a critical analysis of the theoretical framework deployed by mainstream General Theory of Law curriculums and its shortcomings on explaining relevant areas of the legal practice. Specially, a comparative analysis between positivist and postpositivist models is attempted in order to show the better performance of the latter where constitutional matters are involved.